Sweet's syndrome - Piyush G Limdiwala; Shilpa J Parikh; Jigna S Shah (Wolters Kluwer Medknow Publications, 2014)
Acute febrile neutrophilic dermatosis or Sweet's syndrome (SS) is characterized by painful, erythematous plaques of rapid onset accompanied by fever. The etiology of SS is unknown and it may be associated with antecedent infections, malignancies, autoimmune diseases, drugs and vaccines, upper respiratory or gastrointestinal infection, pregnancy, inflammatory bowel disease as well as chemotherapy or idiopathic. The standard therapy for SS is systemic corticosteroids. We report a rare case of 19-year-old young male patient with complaint of severe ill-defined type of pain in both jaws associated with plaques and papules on extensor surfaces of upper and lower extremities with bodyache and myalgia. Histopathological examination suggested perivascular neutrophilic infiltration with scattered eosinophils. Sweet syndrome has rare oral manifestations secondary to hematological changes. It can also present as a paraneoplastic syndrome (malignancy-associated form of condition, which is most commonly related to acute myelogenous leukemia), which leads to poor prognosis and thus it requires careful examination, early diagnosis and long-term follow-up.